Secretion of Angiogenic Growth Factors by Villous Cytotrophoblast and Extravillous Trophoblast in Early Human Pregnancy - Lash, G.E.; Naruse, K.; Innes, B.A.; Robson, S.C.; Searle, R.F.; Bulmer, J.N. (Placenta (Eastbourne), 2010)
Angiogenesis is a key feature of placental and uterine development in early pregnancy. We hypothesized that trophoblast cells produce angiogenic growth factors, and that expression differs between villous cytotrophoblast (CTB) and extravillous trophoblast (EVT) cells. Fourteen angiogenic growth factors were measured by multiplex growth factor analysis or ELISA in tissue culture supernatants from EVT and CTB from pregnancies at 8–10 and 12–14 weeks' gestation. Gestational age and cell type differences were observed. EVT and CTB are major producers of angiogenic growth factors that likely contribute to placental vascular development and spiral artery remodeling.